INTEGRATED IPA MODULE BASED ON GUIDED INQUIRY ON MATERIALS FOOD ADDITIVES TO INCREASE LEARNING OUTCOMES - Tiurlina Siregar; Siti Patimah (Jurnal Ilmu Pendidikan Indonesia, 2021)
This study aims to determine the feasibility of developing an integrated science module and student learning outcomes using an integrated science module based on guided inquiry on food additives. Research Methods Research and Development. The research sample was carried out in class VIII B of SMP Negeri 1 Sentani with a total of 30 students. The results showed that the feasibility of an integrated science module based on guided inquiry on food additives in the category of very suitable for use as teaching materials and improving student learning outcomes with the n-Gain test obtained an average of 0.74 in the high category.